Influence of various mineral supply on sweet corn root development - Orosz, F.; Terbe, I. (International Journal of Horticultural Science, 2006)
Investigations into root strength have assumed particular importance with the emergence of American rootworm (Diabrotica virgifera-virgifera) as the number one pest, mainly as a result of monocultural production. Three treatments were applied in the trial: zero control treatment, treatment "A" (g/m2): 4, 47 N + 7, 89 P205 + 19, 74 K20 and treatment "B"(g/m2): 8, 94 N + 15, 78 P205 + 19, 74 K20. Measurements were made to find out whether the treatments had produced any significant difference between the root strength of the two varieties (normal sweet Puma F I and super sweet Dessert R75 Fl) at the two dates of measurement (tasseling, milk stage) in the year 2003. The treatments with a high phosphorous ratio resulted in an apparent increase in root strength with both varieties. There was a detectable difference in root strength also between the two points of measurement, suggesting that root development had remained stable. The treatments produced significant increase not only in the root strength but also in the yields of both varieties.